The Seroepidemiology of Strongyloides stercoralis Infection in Jamaica - Anique Vanessa Chin; Tamara Thompson; Cobrini S. Denton; John F. Lindo (Journal of Tropical Medicine)
Strongyloides stercoralis is a soil-transmitted helminth which is distributed predominately throughout tropical and subtropical regions and is considered a neglected tropical disease. Due to low larval output, traditional microscopic methods lack sensitivity, especially in areas of low endemicity. Serological assays present an opportunity to study the epidemiology of S. stercoralis in areas of low endemicity such as Jamaica. The current study evaluated the seroprevalence of S. stercoralis in a selected subpopulation in Jamaica. An analysis was conducted on 311 archived serum samples previously submitted for investigating viral infections during a fever epidemic between 2014 and 2015. Randomly selected, anonymized sera were tested for the presence of S. stercoralis IgG antibodies using the AccuDiag Strongyloides IgG ELISA Kit. Data including age, sex, clinical diagnosis, and the geographic location of sample submission were recorded to delineate trends in demographic variables. The seropositivity rate of S. stercoralis was 15.43%. The rate among females and males was 16.45% and 14.47%, respectively (χ2 = 0.2339, p=0.629). The highest rate was found in middle adulthood (31–50 years) (26.53%; 13/49). The seroprevalence of S. stercoralis was significantly highest in a rural Regional Health Authority (33.33%; 14/42) and least within an urban Health Authority (9.71%; 17/175). Exposure to S. stercoralis appears to be highest in the rural Regional Health Authorities with an island-wide exposure rate of 15.43%. The rapid ELISA testing method for the detection of IgG antibodies to S. stercoralis used in this study may be useful as part of a combined approach to elucidate the epidemiology of this soil-transmitted parasite in Jamaica.